Brugada Syndrome in the Pediatric Population: Diagnostic Challenges and Clinical Outcome—Results of the German Multicenter Study COGIA - Lea Lippert; Tobias Burkard; Franziska Markel; Volker Debus; Fridrike Stute; Anna Kamphues; Robert Dalla Pozza; Stefan Rupp; Maria B. Gonzalez y Gonzalez; Claudia Junge; Majed Kanaan; Kirstin Hoff; et al. (Journal of Cardiovascular Electrophysiology, 2026)
ABSTRACT Introduction Diagnosis and treatment of children and adolescents with suspected Brugada syndrome (BrS) is challenging. Aim of the study was to evaluate the applicability of current diagnostic criteria for pediatric patients with suspected BrS in the German multicenter study COGIA and to assess clinical outcome. Methods Data analysis of 76 pediatric patients from 12 German tertiary care centers. Primary outcome was defined by the occurrence of a major arrhythmic event (MAE), secondary outcome by symptoms, pharmacotherapy and implantation of devices. MAE was defined as sudden cardiac death (SCD), aborted cardiac arrest (ACA) and appropriate implantable cardioverter‐defibrillator (ICD) therapy. Results Criteria for BrS diagnosis were fulfilled in 39/76 pediatric patients (51.3%) according to ESC Guidelines, including 34 patients (44.7%) according to Shanghai Score. Genetic testing identified a (likely) pathogenic SCN5A variant in 31/66 tested children (47.0%) (14/30 with clinical diagnosis (46.7%) and 17/36 without clinical diagnosis (47.2%)). Twenty‐four patients (31.6%) showed a spontaneous type 1 ECG pattern, in 6 patients (7.9%) it was induced by fever. Ajmaline challenge was positive in 19/25 patients (76.0%). Syncope occurred in 15 patients (19.7%) and an ICD was implanted in 7 pediatric patients (9.2%). Four patients (5.3%) experienced a MAE (ACA), all of them fulfilling diagnostic criteria. “Symptoms at first consultation” was identified as an independent risk factor for MAE in the whole cohort (HR = 11.3, p = 0.04). Conclusion Establishing the diagnosis of BrS remains challenging in the pediatric cohort. MAE occurred in 5.3% of patients with suspected BrS. Symptoms at first consultation increased risk for MAE. Clinical Trial Registration: The study is registered at the German Clinical Trial Register (DRKS) of the Federal Institute for Drugs and Medical Devices (BfArM), DRKS‐ID DRKS00028138.